E-proctoring Gone Wrong - Chareka, Missy (Canadian Perspectives on Academic Integrity, 2021)
The 2020-2021 academic year saw an unprecedented rise in the use of e-proctoring, for the facilitation of online exams. With that also came unprecedented challenges and issues. This presentation will be a survey of some of the issues and questions regarding the use of e-proctoring. Some issues that will be addressed include accessibility issues and the use of artificial intelligence and its ethical problems. The presentation will then focus on the question of academic integrity, and more specifically how academic integrity breaches were handled by various institutions across North America. The presentation will showcase how e-proctoring introduced a new host of problems in the area of academic integrity adjudication and a discussion will follow on considerations for the future of e-proctoring and the maintenance of academic integrity in academia.